Pengaruh Tunjangan Kinerja Terhadap Kinerja Pegawai pada Kantor Imigrasi Kelas II Tanjung Uban - SITI UTARI, DIAH; Rinah, Sri Ambar; Irwansyah, Muhammad (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Tanjung Uban Class II Immigration Office as an agency that has a strategic function in terms of immigration services and immigration control for foreigners and passport services for Indonesian citizens. Therefore, the government provides additional benefits called remuneration. With the remuneration, employees are expected to be able to improve performance. However, there is no benchmark or basis for knowing whether this remuneration affects the level of performance of employees at the Tanjung Uban Class II Immigration Office. This research uses descriptive research method using a quantitative approach. The technique used in data collection is observation and questionnaire or questionnaire. This study aims to determine how much influence between the remuneration of employee performance at the Tanjung Uban Class II Immigration Office. Data retrieval is done by proportional random sampling method with total samples n = 46. Significant test results show that the calculated t value is greater than t table (5.791 > 2,0129), then there is a significant effect between remuneration and employee performance at the Tanjung Uban Class II Immigration Office. It can be concluded that the variable X (remuneration) has a  positive influence on the variable Y (performance).The coefficient of determination (R2) is used to measure how far the model's ability to explain the dependent variable. The SPSS output ver.22 above shows that R is 0.658 or 65.8% which means that the independent variable (remuneration) affects the dependent variable (employee performance) by 65.8% and the remaining 34.2%, which is estimated by other factors.